1991
DOI: 10.1161/01.str.22.12.1592
|View full text |Cite
|
Sign up to set email alerts
|

Myoendothelial junctions in human brain arterioles.

Abstract: Background: The purpose of this work was to determine whether myoendothelial junctions were present in human brains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…In this branch of the middle cerebral artery, interendothelial cell and intersmooth-muscle cell gap junctions could be observed, and in addition myoendothelial gap junctions were present suggesting that both homo-and heterocellular coupling exists between the different cell types; these findings are similar to those described in human cerebral arteries. 23 Because both IK Ca and SK Ca were expressed in the endothelium, and SLIGRL stimulates an endothelium-dependent response through a receptor coupled by G q/11 to rises in intracellular Ca 2ϩ , the likely explanation is that endothelial cell hyperpolarization may be transmitted to the muscle layers through myoendothelial gap junctions. However, it appears that when considering nonnuclear staining, both the SK2 and SK3 channels are very diffuse within the endothelium, suggesting low levels of expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this branch of the middle cerebral artery, interendothelial cell and intersmooth-muscle cell gap junctions could be observed, and in addition myoendothelial gap junctions were present suggesting that both homo-and heterocellular coupling exists between the different cell types; these findings are similar to those described in human cerebral arteries. 23 Because both IK Ca and SK Ca were expressed in the endothelium, and SLIGRL stimulates an endothelium-dependent response through a receptor coupled by G q/11 to rises in intracellular Ca 2ϩ , the likely explanation is that endothelial cell hyperpolarization may be transmitted to the muscle layers through myoendothelial gap junctions. However, it appears that when considering nonnuclear staining, both the SK2 and SK3 channels are very diffuse within the endothelium, suggesting low levels of expression.…”
Section: Discussionmentioning
confidence: 99%
“…5A). This finding suggest that myoendothelial gap junctions, which have been demonstrated to be present in resistance arteries and arterioles from different vascular beds (2,14,18,28), allow intercellular electrical coupling between endothelial and smooth muscle cells (10,13,14,20,39,40). Recent studies also demonstrated inhibition of ACh-induced, EDHF-type dilations in rabbit iliac (32) and mesentery arteries (9) and perfused murine hindlimb vessels (8) with structurally different gap junction inhibitors.…”
Section: Discussionmentioning
confidence: 96%
“…Regional variation in the distribution of MEGJs, as found here in the RFA and in mesenteric arteries [31] could further add to the problem of detecting MEGJs using random sections. Indeed, the identification of MEGJs in studies employing random sections is limited to the carotid artery of the rabbit [39] and cerebral arterioles of humans [40]. However, through serial section electron microscopy these small junctions have been identified in numerous arteries of the rat and mouse, correlating well with their involvement in vascular function [28,29,31,41].…”
Section: Discussionmentioning
confidence: 99%